(3GdOjhGf GdYLjH hGdCSdhH GdZQjHs - (3ZQS GdOjf GdNdjdj , eMeO (B((3ZQS GdOjf(B) (3Hf CMeO GdCfUGQj GdNdjdj GdeOfj, ZQS GdOjf,J (B1057 (3g` s
(3BNQgG (B:s
(3jfJgi Edi MQa GddGe s
(3LYd bhGai cd bUjOI eJMOI ai GddaX eJZGjQI ai GdeYfis
(3hLYd ChGFd GdCHjGJ eaSQI ddaX GdPi hbY ai GdbGajI hgh eQJH Ydi MQha GdeYLes
(3hgh LedI bUGFOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B10 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B112s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B462 s
Keywords: (3GdCOHs